Secondary siRNAs in Plants: Biosynthesis, Various Functions, and Applications in Virology - Sanan-Mishra, Neeti; Abdul Kader Jailani, A.; Mandal, Bikash; Mukherjee, Sunil K. (Frontiers in Plant Science, 2021)
The bulky components of RNA silencing include both transitive and systemic small RNAs which are technically called secondary sRNAs. Double stranded RNAs trigger systemic silencing pathways to negatively regulate gene expression. The secondary siRNAs generated as a result of transitive silencing also play a substantial role in gene silencing especially antiviral activity. Before being transmitted across cells, siRNAs need to be amplified. In this review, we first describe the discovery and pathways of transitivity with emphasis on RNA dependent RNA polymerases followed by description on the short range and systemic spread of silencing. We also provide an in-depth view on the various size classes of secondary siRNAs and their different roles in RNA silencing including their categorization based on their biogenesis. The other regulatory roles of secondary siRNAs in transgene silencing, virus induced gene silencing, transitivity and trans-species transfer have also been detailed. The possible implications and applications of systemic silencing and the different gene silencing tools developed are also described. The details on mobility and role of secondary siRNAs derived from viral genome in plant defense against the respective viruses are presented in details. This entailed the description of other compatible plant-virus interactions and the corresponding small RNAs that determine recovery from disease symptoms, exclusion of viruses from shoot meristems and natural resistance. The last section presents an overview on the usefulness of RNA silencing for management of viral infections in crop plants.